Influence of Yoga-based program on health satisfaction in the Mongoloid patients diagnosed with type 2 diabetes mellitus - N Ibohal Singh; Balaram Pradhan; Mangesh Pandey; Niranjan Parajuli; Achouba Ksh Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Patients diagnosed with type 2 diabetes mellitus (T2DM) have to live with this condition throughout the life. Minimizing the complications and enhancing the overall health of patients with T2DM are the major global challenges. Improving the health satisfaction in diabetes patients can enhance their adherence to treatment and could minimize the complications of the disease. Aim: The study evaluated the effects of Yoga along with treatment as usual on health satisfaction in T2DM patients of Mongoloid. Methods: The design of the present study is randomized control trial. This study was approved by the institutional ethical committee of Jawaharlal Nehru Institute of Medical Sciences (JNIMS), Imphal, Manipur. Written informed consent was obtained from the participants before enrolling to the study. Four hundred and fifty diabetes patients belonging to Mongoloid race were screened for inclusion and exclusion criteria at the outpatient clinic of the Department of Endocrinology at JNIMS, Imphal, Manipur. Out of them, 310 participants (age range 25-80 years) were recruited for the study purpose for fulfilling the inclusion and exclusion criteria. Patients were randomized into Yoga along with treatment as usual group (N = 155) and treatment as usual group (N = 155). The Yoga along with treatment as usual group was prescribed oral antiglycemic agents and yoga intervention for 16 weeks. The treatment as usual group was prescribed oral antiglycemic agents only without any exercise during the period. Participants were assessed at baseline and at the end of the intervention by using the Current Health Satisfaction Questionnaire (CHES-Q). Final analysis included 151 participants in the Yoga along with treatment as usual group and 153 in the treatment as usual group. Four participants in the Yoga group and two participants in the control group were excluded from the study for discontinuing the treatment at the endocrinology department. Results: Within-group analysis showed a significant improvement in all the subfactors of health satisfaction in both groups. There was a significant interaction (groups × times) in all domains of CHES-Q, except satisfied with the current level of energy, satisfied with current ability to sleep, satisfied with current blood sugar levels, and satisfied with current mood. Conclusion: The findings of the present study showed improvement in health satisfaction in both groups. Results also indicated that Yoga along with treatment as usual is better compared to the control group. However, future studies considering clinical and anthropometric parameters along with health satisfaction are required to support the current findings.